Spatial Variability and Concentration of Arsenic in the Groundwater of a Region in Southwest Buenos Aires Province, Argentina - Paoloni, Juan Dario (2000)
Arsenic is widely found in the natural environment mainly as an outcome of processes related to vulcanicity but also as a consequence of anthropogenic use of inorganic forms such as arsenate and arsenite (Varillas et al. 1997). Material of volcanic origin is transported in suspension in the atmosphere and deposited as lenticular layers in the sediment on plains (Bolzicco et al. 1997). These layers undergo a washing process and the resulting fragments are subsequently mobilized by means of various infiltration and straining mechanisms, ending up in surface and groundwater (Bhumbla and Keefer 1994). Chronic endemic hydro-arsenism is caused by the consumption, over prolonged periods, of water containing higher than normal concentrations of arsenic (Biagini et al. 1995). It is estimated that some 30 μg of arsenic per kilo of body weight is incorporated into the human organism daily, solely on the basis of the average arsenic content in food (Formigli et al. 1997). The World Health Organization (WHO) (1995) estimated that the average daily intake of inorganic arsenic from water reaches similar levels to that ingested via foodstuffs. This serious public health hazard is known to exist in Argentina (Salvador 1987) and was already recognized early this century (Ayerza 1978).